Clinical Team Perspectives on the Psychosocial Aspects of Transition to Adult Care for Patients With Childhood‐Onset Systemic Lupus Erythematosus. Issue 1 (10th December 2020) - Bitencourt, Nicole; Kramer, Justin; Bermas, Bonnie L.; Solow, E. Blair; Wright, Tracey; Makris, Una E.
Abstract : Objective: The transition from pediatric to adult care for youth with childhood‐onset systemic lupus erythematosus (SLE) is a vulnerable period. Adverse outcomes during this transition include gaps in care, unscheduled health care utilization, loss of insurance, and high disease activity. The objective of this study was to examine the clinical care teams' perspective on the psychosocial factors associated with transition outcomes, which are poorly understood in this population. Methods: We conducted in‐depth interviews with clinical care team members who interact with childhood‐onset SLE patients during transfer from pediatric to adult rheumatology. A semistructured interview guide was used to prompt participants' perspectives about the psychosocial factors associated with the transition process for patients with childhood‐onset SLE. Audio recordings were transcribed and analyzed using the constant comparative method. We stopped conducting interviews once thematic saturation was achieved. Results: Thirteen in‐depth interviews were conducted. Participants included pediatric rheumatologists (n = 4), adult rheumatologists from both academic and private practice settings (n = 4), nurses (n = 2), a nurse practitioner, a social worker, and a psychologist. We identified several themes deemed by clinical care teams as important during the transition, including the impact of the family, patient resilience and coping mechanisms, the role of mental health and emotional support, and the need for education, peer support, and social connectedness. Conclusion: We identified several psychosocial themes that clinical team members believe impact the transition of patients with childhood‐onset SLE into adult care. The role of parental modeling, youth resilience, mental health and emotional care, improved childhood‐onset SLE education, and structured peer support and social connectedness are highlighted, which may be amenable to interventions.